An Approach to the Synthesis of Spiro[indene-pyridoisoquinoline] Derivatives via 1,4-Dipolar Cycloaddition of Isoquinoline and Acetylene Esters, and (1,3-Dihydro-1,3-dioxo-2H-inden-2-ylidene)malononitrile - Alizadeh, Abdolali; Sadeghi, Vahideh; Bayat, Fahimeh; Zhu, Long-Guan (Helvetica chimica acta, 2014)
A concise and efficient approach to the spiro‐tetrahydroisoquinoline derivatives has been developed by 1,4‐dipolar cycloaddition of zwitterions resulting from isoquinoline and acetylene esters and (1,3‐dihydro‐1,3‐dioxo‐2H‐inden‐2‐ylidene)malononitrile in MeCN at room temperature. The significance of this method lies in good yields and ease of product purification, and no inert atmosphere is required. The structures of the products were confirmed spectroscopically (IR, 1H‐ and 13C‐NMR, and EI‐MS) and by elemental analyses. A plausible mechanism for this reaction is proposed (Scheme).